Elevated DMBT1 levels in neonatal gastrointestinal diseases - Müller, Hanna; Renner, Marcus; Helmke, Burkhard Maria; Mollenhauer, Jan; Felderhoff-Müser, Ursula (Histochemistry and cell biology, 2016)
Deleted in malignant brain tumor 1 (DMBT1) is involved in innate immunity and epithelial differentiation. Previous studies in adults indicated a strong intestinal expression of DMBT1 and an important role in inflammatory bowel diseases. Here, we analyzed the DMBT1 expression in the fetal gastrointestinal system depending on gestational age and in patients with necrotizing enterocolitis (NEC), volvulus, intestinal perforation (IP), or herniation, representing typical diseases of preterm and term infants. We used immunohistochemistry and RNA in situ hybridization to detect DMBT1 protein and mRNA in fetal tissues, supplemented by postmortem analysis of DMBT1 expression in died newborns and analysis of surgically removed tissues. DMBT1 expression is detectable in the early developmental stages of the gastrointestinal system. In NEC, volvulus, IP, or herniation, characterized by high systemic inflammatory responses, DMBT1 expression is strongly increased. High DMBT1 expression was also found in the bile ducts of older infants with sepsis or cholestasis. The study shows that DMBT1 expression is observed in the developing gastrointestinal system and up-regulated in infants with NEC, volvulus, IP, and herniation. DMBT1 may play a role in epithelial differentiation and local innate immunity during neonatal inflammatory bowel processes.